Psychometric Properties of an Instrument for Assessing University Administrators' Knowledge on Gender-Based Violence - Elisabeth Meloni Vieira; Maria Paula Panúncio-Pinto; Deíse Camargo Maito; Maria Carmen Martinez (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To evaluate the factorial structure of the instrument measuring university administrators' knowledge of gender-based violence. Methods: This cross-sectional methodological study was conducted from August to November 2020 with 101 university administrators. Data on demographic and functional characteristics were collected, and the "QUEST VBG UNIV" instrument was applied. Descriptive analysis was performed, the structure of the questionnaire was assessed using exploratory factor analysis (EFA), and the stability of the factors was verified through ORION and FDI tests. Results: Of the original 38 items across the 4 sections of the questionnaire, 19 were retained within 2 factors, with appropriate factor loadings. Factor 1 had an explained variance of 15.69%, and Factor 2 had an explained variance of 9.10%. The reliability was deemed satisfactory (ORION > 0.900, FDI > 0.900). Conclusions: The questionnaire presented a valid and reliable factorial structure for measuring knowledge about gender-based violence, thereby representing a suitable option for situational assessments in universities.